Dynamic electrophysiological changes in abnormal brain cavities post-ischemic stroke - Kilic, Ugur; Laughlin, Myles Mc; Deng, Zhengdao; Deprez, Marjolijn; Seminck, Nina; Asamoah, Boateng; Nuttin, Bart (Frontiers in Neuroscience, 2025)
IntroductionStroke is a global health challenge and the leading cause of long-term disability. While survival rates have improved, effective treatments for post-stroke impairments remain lacking. A novel approach to address this unmet need involves targeting the cavities that develop after ischemic events, referred to as abnormal brain cavities (ABCs), for post-stroke neuromodulation. Despite their potential significance, ABCs have not been systematically studied, creating a gap in understanding their role in recovery and therapeutic strategies. This study represents the first investigation into the electrophysiological properties of ABC walls.MethodsTo explore this, we developed an ABC model in anesthesized rats (male, n = 11) through controlled aspirations of the forelimb area of the motor cortex. We recorded local field potentials (LFPs), event-related potentials (ERP), and spiking activity across various conditions, including healthy, acute, and chronic phases from different anatomical locations of the ABC wall.ResultsOur findings revealed significant effects of both location and condition on oscillatory power across different frequency bands. We observed significant decreases in power across different conditions (p < 0.0001), and this decrease varied in different locations. Similarly, our analysis showed significant effects of location and condition on ERP amplitudes, revealing a marked reduction in the acute phase (p = 0.001), followed by recovery in the chronic phase (p = 0.007). As the condition progressed to the chronic phase, these ERPs had shorter latencies (p < 0.0001). Notably, our results demonstrated that spiking rates remained consistent, across different conditions.DiscussionThis near-normal single-unit activity suggests that the ABC wall has the potential to serve as an effective interface for neuromodulation. Additionally, the significant effects of location on our outcome measures indicates that, location-specific electrophysiologic signatures exist within the ABC wall, which could guide targeted stimulation strategies. Overall, this study underscores the need for further research into stimulation techniques targeting ABCs to facilitate recovery in stroke patients, as the ABC wall presents a promising opportunity for direct access to lesioned brain areas.